Exercise-Induced Adaptations to Adipose Tissue Thermogenesis - Vidal, Pablo; Stanford, Kristin I. (Frontiers in Endocrinology, 2020)
Exercise training results in beneficial adaptations to numerous tissues and offers protection against metabolic disorders including obesity and type 2 diabetes, and multiple studies have indicated that both white (WAT) and brown (BAT) adipose tissue may play an important role to mediate the beneficial effects of exercise. Studies from both rodents and humans have identified exercise-induced changes in WAT including increased mitochondrial activity and glucose uptake, an altered endocrine profile, and in rodents, a beiging of the WAT. Studies investigating the effects of exercise on BAT have resulted in conflicting data in terms of mitochondrial activity, glucose uptake, and thermogenic activity in rodents and humans, and is an important area of investigation. This review discusses the exercise-induced adaptations to WAT and BAT, distinguishing important differences between rodents and humans and highlighting the latest studies in the field and their implications.